HARMONI KEWAJIBAN DAN HAK BAGI PENYANDANG AUTISME MELALUI IMPLEMENTASI CONVENTION THE RIGHT OF PERSONS WITH DISABILITIES (CPRD) DALAM PENDIDIKAN DI SLB NEGERI AUTIS SUMUT - Yunita, Sri; Agnes, Agnes; Angelica, Angelica; Enzelly, Enzelly; Gloria, Gloria; Veronika, Veronika; Yesika, Yesika (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
Currently, there are many private special needs schools in the province of North Sumatra, but very few public special needs schools, although not everyone with special needs has much money financially. Therefore, there are still many poor children who do not get the right to school. In 2018, the SLB Autistic Sumut was built. This SLB is one of three SLB at the provincial level in North Sumatra Province and the only one in Medan. Building a school will be very beneficial for poor people who have autistic families so that their children can experience school. The purpose of this study was to find out (1) the rights and obligations of persons with disabilities in the SUMUT State SLB schools (2) to determine the implementation of the SUMUT State SLB (3) implementation, learning planning, assessment and evaluation. Facilities students and teachers work there. This study used a descriptive qualitative method. Observations and interviews with one of the lecturers at SLB Negeri SUMUT were used as data collection techniques. Based on the information received, there are 27 teachers and 9 employees/staff, and 75% of students with autism. Based on the research conducted, it can be concluded that rights and obligations have been harmonized in SLB Negeri Autism